Explaining very early acute mild traumatic brain injury after motor vehicle collision pain variability: additive value of pain sensitivity questionnaire. (20th May 2020) - Kuperman, Pora; Granovsky, Yelena; Bahouth, Hany; Fadel, Shiri; Ben Lulu, Hen; Bosak, Noam; Buxbaum, Chen; Sprecher, Elliot; Crystal, Shoshana; Granot, Michal
Abstract: Introduction and Objectives: Chronic pain is a common postcollision consequence. Wherein, a clearer understanding of acute pain can help stem the acute-to-chronic pain transition. However, the variability of acute pain is only partially explained by psychophysical pain characteristics as measured by quantitative sensory testing. The Pain Sensitivity Questionnaire (PSQ) may reflect inherent psychocognitive representations of patient's sensitivity and thus may reveal less-explored pain dimensions. In the vein of the biopsychosocial approach, this study aimed to explore whether PSQ holds additive value in explaining head and neck pain reports in very early acute-stage mild traumatic brain injury (mTBI) after collision, above the use of psychophysical assessment. Methods: Study cohort (n = 130) consisted of mTBI patients (age range 19–66, 57 F) after accident with area-of-injury pain of at least 20 on the day of testing (mean pain 58.4 ± 21.6, range 20–100 Numerical Pain Scale) who underwent clinical, psychophysical, and pain-related psychological assessment within 72-hour after injury. Results: Pain Sensitivity Questionnaire scores were significantly correlated with acute clinical, psychophysical, and pain-related psychological measures. Regression model ( R 2 = 0.241, P < 0.001) showed that, together, age, sex, high PSQ, enhanced temporal summation, and less-efficient conditioned pain modulation explained head and neck pain variance. This model demonstrated that the strongest contribution to degree of postinjury pain was independently explained by PSQ (ß = 0.32) and then pressure pain threshold-conditioned pain modulation (ß = −0.25). Conclusion: Appraisal of cognitive daily-pain representations, by way of memory and imagination, provides an additional important dispositional facet to explain the variability in the acute mTBI postcollision clinical pain experience, above assessing nociceptive responsiveness to experimentally induced pain.